Trends in Safety Culture Research: A Scopus Analysis - Al-Baraa Abdulrahman Al-Mekhlafi; Noreen Kanwal; Mohammed Nasser Alhajj; Ahmad Shahrul Nizam Isha; Abdullah O. Baarimah (Safety, 2025)
Safety culture plays a vital role in creating safer work environments, making its understanding important. This paper comprehensively analyzes safety culture research trends through a bibliometric study using the Scopus database. This study provided a full insight by analyzing 7058 papers published between 1978 and 2023, employing the PRISMA method and VOSviewer 1.6.19 for bibliometric mapping. The USA, England, China, and Australia are the leading contributors, with Johns Hopkins University being the most active institution. Approximately 75% of publications are co-authored, indicating strong collaboration in this field. Guldenmund (2000) is the most referenced work in safety culture research. Based on the results, this work identifies significant geographical gaps, particularly in Oceania, South America, the Middle East, Southeast Asia, and Africa, as well as underexplored sectors such as transportation, logistics, energy, sports, education, and construction. The COVID-19 pandemic has profoundly impacted research in this area, particularly healthcare, while potentially diverting attention from other critical sectors. This study contributes a fresh perspective on the trends of safety culture research, offering valuable insights for scholars and practitioners. Additionally, it highlights the importance of interdisciplinary collaboration in addressing the unique challenges faced by safety culture across diverse industries and regions.